Семантичні аспекти полісемічних іменників у електронному Словнику української мови в 20-ти томах - Бондар, Т. (Лексикографічний бюлетень, 2011)
The article examines lexicographic representation of polysemantic nouns in the electronic Dictionary of Ukrainian Language in 20 volumes. Statistic analysis shows that the Dictionary contains 77217 registered nouns, 12127 of which (approximately 15%) are polysemantic. Without terminology the number of polysemantic nouns increase to approximately 40%. The ability of words to have several meanings is one of linguistic universals. Lexical polysemy is determined, on the one hand, by the outside world as a set of objects and phenomena, and on the other hand, by the limited vocabulary of any language, which is associated with the principle of linguistic economy. While separating the primary meaning and derivative meaning, it is necessary to consider the connection between lexical meaning, linguistic and extralinguistic factors: paradygmatic, syntagmatic and epidigmatic links. Despite the fact that the phenomenon of polysemy is complex and discrete, the most effective presentation of it is found in the dictionaries as a set of specific hierarchical meanings and models of semantic derivation. Semantic aspects of polysemantic nouns are analyzed involving the theory of semantic states, which allows modelling semantic structure of polysemantic nouns and differentiate the semantic variants of ambiguous words.